Rancang Bangun Sistem Transmisi Belt dan Pulley Pada Mesin Crusher Plastik High Density Polyethylene (HDPE) - Pramudi, Ganjar; Wibowo, Alif Sebrio (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
High-Density Polyethylene (HDPE) plastic is one of the most widely used types of plastic, commonly found in products such as bottles, containers, and pipes. However, if not managed properly, HDPE plastic waste poses a significant environmental challenge. An HDPE plastic crusher machine is a tool designed to shred HDPE plastic waste into fine powder, facilitating recycling and its use in composite materials. The objective of this research is to design and construct an efficient and effective HDPE plastic crusher machine. The HDPE plastic crusher machine features a rotary knife and a robust steel frame. The rotary blade is crafted from a hard, sharp material, while the steel frame provides support for the machine's body and drive motor. The machine is powered by a 3 HP electric motor operating at a speed of 1400 RPM. Power transmission is achieved through a belt and pulley system. The machine functions by transferring power from the main 3 HP electric motor to the shaft of the crusher knife. Direct testing of the HDPE plastic crusher machine was conducted using shredded HDPE plastic. The testing process was divided into two types: one without HDPE plastic and one with HDPE plastic. The results indicated that the machine produced 100 grams of fine powder in 30 minutes. The belt and pulley transmission system demonstrated a maximum tension of 216.5 N and a working tension of 176.4 N.